Bulk ZnO: Current Status, Challenges, and Prospects - Avrutin, Vitaliy; Cantwell, Gene; Zhang, Jizhi; Song, J. J.; Silversmith, Donald J.; Morkoc, Hadis (Proceedings of the IEEE, 2010)
Rediscovered in the last decade, zinc oxide (ZnO) shows a great potential for many optoelectronics and to some extent microelectronics applications. However, a clear majority of effort expended in this fast developing field has been limited to heteroepitaxial structures grown on foreign substrates with lattice-parameter and thermal-expansion mismatch with ZnO which is detrimental. Recognizing the importance, the effort has shifted to include developing technologies capable of producing freestanding ZnO wafers in large-scale for ZnO based device applications, which is the subject matter of this manuscript. Three competing approaches - hydrothermal method, melt growth (modifications of the well known Bridgman technique), and seeded vapor transport growth - have now reached or are approaching commercial viability. In this article, we discuss the progress, outstanding problems, and prospects of these growth methods employed for commercial manufacturing of ZnO wafers.